Results of Acetabular Microfracture in Patients undergoing FAI surgery are Strongly Correlated with Age (142). Issue 10 (31st October 2021) - Westermann, Robert; Nepple, Jeffrey; Garrido, Cecilia Pascual; Clohisy, John; Larson, Christopher
Objectives: Full-thickness cartilage injury is not uncommon in patients undergoing primary treatment of Femoroacetabular impingement (FAI). Treatment of these lesions with microfracture is commonly performed. However, the outcomes of these procedures relative to other patients undergoing FAI surgery is not well established and the literature on this topic is limited to small, retrospective single surgeon studies. The purpose of the present study was to evaluate outcomes of patients who underwent concurrent FAI correction and acetabular microfracture and to identify predictors treatment failure. Methods: A prospective multicenter cohort study of the treatment of FAI was performed. A total of 760 hips undergoing primary FAI surgery were enrolled. Inclusion criteria were primary FAI surgery, Tonnis 0 or 1 osteoarthritis grade, and age between 16 and 55 years. A total of 61 hips underwent treatment of full-thickness acetabular cartilage lesions with microfracture, with 55 (90.2%) having follow-up greater than 1 year (mean 4.0 years). This group had a mean age of 35.0+ 10.1 years, BMI of 27.2+ 4.2, and included 81.8% (45/55) males. A comparison cohort of 492 hips undergoing primary FAI surgery without treatment of acetabular full-thickness cartilage was utilized. Baseline, intraoperative, and follow-up data was recorded including the modified Harris hip score (mHHS) and HOOS domains of pain, ADLs, sports and recreation, symptoms, and quality of life. Composite failure was characterized by reoperation [total hip arthroplasty (THA) or revision surgery] or clinical failure (failure to meet either MCID or PASS for mHHS). Age was assessed in 5 year intervals. Students t-test was used for continuous variables and chi squared were used for categorical variables. A p value less than 0.05 was considering significant. Results: Hips undergoing acetabular microfracture were more likely (compared to comparison cohort) to be male (81.8% vs. 40.9%, p<.001) older (35.0 vs. 29.9 years, p=0.001), had higher BMI (27.2 vs. 25.0, p=.001), and greater alpha angle (69.6 vs. 62.3, p<.001). In the microfracture cohort, 12.7% of patients progressed to THA (compared to 3.0% in comparison cohort, p=.001), while the rate of composite failure was similar to the comparison cohort (29.1% vs. 26.0%, p=.618). Age was highly correlated with the risk of THA and composite failure. The rate of THA for patients <35, 35-40*, and >40 years* of age was 0%, 20.0%, and 22.7% p=.016*), while the rate of composite failure in these groups was 17.4%, 20.0% and 45.5%, respectively (p=.029*). Hips greater than 35 years of age demonstrated inferior HOOS outcomes for domains of pain, ADLs, sports and recreation, QOL, and symptoms and SF-12 physical component scores(Table 1). Conclusions: The results of acetabular microfracture in patients undergoing FAI surgery at a mean follow-up of 4.0 years postoperatively are strongly correlated with age. Patients under 35 years of age demonstrate excellent outcomes with low rates of revision or progression to THA. Acetabular microfracture should have a limited to absent role in patients over the age of 40.